Model Koordinasi Logistik Kemanusiaan di Indonesia dengan Melibatkan Sektor Swasta - Ferdiarto Limantoro; I Gede Agus Widyadana; Herry Christian Palit (Jurnal Titra, 2015)
This study was conducted to give the proposed model of humanitarian logistics coordination for the handling of natural disasters in Indonesia by involving the private sector. The private sector, involved in disaster management, is DHL. The analysis techniques used are the competitive profile matrix to evaluate the performance of each agency involved and RASIC analysis to determine the role of each institution in each activity. The results showed that the private sector is still less involved in Indonesia’s disaster management and the role of some institutions in some activity is still not quite right. DHL is proposed to be involved because it has sufficient capacity to be involved in disaster management. Activities that can be roled by DHL are involving in the delivery and distribution of relief and to help receive relief from foreign parties. Activities that need to be changed is the provision of funds, the making standardization relief, and assessment.